Positive Electrode and Energy Storage Device
Patent Information
- Application Number
- JP2021020633
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-02-12
AI Technical Summary
【0014】 本発明によれば、蓄電デバイスのセル抵抗を減少させるとともに、耐久性を向上させることが可能な正極を提供することができる。
Smart Images

Figure 0007631019000003 
Figure 0007631019000004 
Figure 0007631019000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode and an electricity storage device. [Background technology]
[0002] Lithium ion secondary batteries have been widely used as high energy density storage devices. The lithium ion secondary battery has a structure in which, for example, a separator is present between a positive electrode and a negative electrode, and an electrolyte is filled in the lithium ion secondary battery. The positive electrode has a structure in which, for example, a positive electrode mixture layer is formed on a positive electrode current collector.
[0003] Patent Document 1 describes a method in which a dispersion liquid of dielectric particles having a relative dielectric constant of 500 or more and a particle size of 200 nm or less is impregnated into a positive electrode current collector on which a positive electrode mixture layer is formed, thereby disposing the dielectric particles inside the positive electrode mixture layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-119180 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, since dielectric particles with a particle size of 200 nm or less are prone to aggregation, if a large amount of such dielectric particles are used, the proportion of electrolyte in contact with the dielectric particles decreases due to aggregation. Therefore, even if an electric field generated inside a lithium-ion secondary battery acts on the dielectric particles, the effect of the dielectric polarization of the dielectric particles to improve the degree of dissociation of the supporting salt in the electrolyte is insufficient, and there is a problem that the cell resistance increases. In addition, the effect of the dielectric particles to capture the acid present in trace amounts in the electrolyte and the effect of the dielectric particles to stabilize the electrolyte by interacting with the electrolyte are insufficient, so that the corrosion of the positive electrode active material and the decomposition of the electrolyte cannot be suppressed, and as a result, the durability of the lithium-ion secondary battery is reduced.
[0006] An object of the present invention is to provide a positive electrode that can reduce the cell resistance of an electricity storage device and improve its durability. [Means for solving the problem]
[0007] In one aspect of the present invention, a positive electrode has a positive electrode current collector and a positive electrode mixture layer, the positive electrode mixture layer containing a positive electrode active material and dielectric particles, and a peak pore diameter is equal to or smaller than the median diameter of the dielectric particles.
[0008] The positive electrode mixture layer may have a content of the dielectric particles of 0.1% by mass or more and 2% by mass or less.
[0009] The dielectric particles may have a relative dielectric constant of 20 or greater.
[0010] The positive electrode may have a peak pore diameter of 0.1 μm or more and 0.6 μm or less.
[0011] The positive electrode may have a density of 3.4 g / cc or more.
[0012] The positive electrode active material may have a bimodal particle size distribution.
[0013] Another embodiment of the present invention is an energy storage device that includes the above positive electrode, a negative electrode, and an electrolyte solution. Effect of the Invention
[0014] According to the present invention, it is possible to provide a positive electrode that can reduce the cell resistance of an electricity storage device and improve the durability. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a graph showing the measurement results of the pore diameter distribution of the positive electrodes of Examples 1 to 5 and Comparative Examples 1 to 3. [Diagram 2] 1 is a SEM photograph of a cross section of a positive electrode of Example 1. [Diagram 3] 1 is an SEM photograph of a cross section of a positive electrode of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described.
[0017] <Positive electrode> The positive electrode of the present embodiment has a positive electrode current collector and a positive electrode mixture layer, and the positive electrode mixture layer contains a positive electrode active material and dielectric particles. The positive electrode of the present embodiment has a peak pore diameter equal to or smaller than the median diameter of the dielectric particles.
[0018] In the positive electrode of this embodiment, the positive electrode mixture layer may be formed on one side of the positive electrode current collector, or the positive electrode mixture layer may be formed on both sides of the positive electrode current collector.
[0019] In this embodiment, since the peak pore diameter of the positive electrode is equal to or smaller than the median diameter of the dielectric particles, the number of pores having a diameter larger than the median diameter of the dielectric particles in the positive electrode composite layer is reduced, and the proportion of the electrolyte in contact with the dielectric particles is increased. Therefore, when an electric field generated inside the electric storage device acts on the dielectric particles, the dielectric polarization of the dielectric particles improves the degree of dissociation of the supporting salt in the electrolyte, and the cell resistance of the electric storage device is reduced. In addition, the effect of the dielectric particles capturing the acid present in trace amounts in the electrolyte and the effect of the dielectric particles interacting with the electrolyte to stabilize the electrolyte can suppress corrosion of the positive electrode active material and decomposition of the electrolyte, thereby improving the durability of the electricity storage device.
[0020] In order to reduce the cell resistance of an electricity storage device and improve its durability, it is preferable to increase the relative dielectric constant of the dielectric particles.
[0021] The peak pore diameter of the positive electrode of this embodiment is preferably 0.1 μm or more and 0.6 μm or less, and more preferably 0.3 μm or more and 0.6 μm or less. When the peak pore diameter of the positive electrode of this embodiment is 0.1 μm or more and 0.6 μm or less, the cell resistance of the power storage device is reduced and the durability is improved.
[0022] The peak pore diameter of the positive electrode of this embodiment can be controlled by adjusting the median diameter of the positive electrode active material or by pressing during the production of the positive electrode.
[0023] The density of the positive electrode of this embodiment is preferably 3.4 g / cc or more, more preferably 3.5 g / cc or more. When the density of the positive electrode of this embodiment is 3.4 g / cc or more, the cell energy density of the electricity storage device is improved. In addition, the effect of the dielectric particles on the electrolyte is improved, and as a result, the durability of the electricity storage device is improved.
[0024] [Dielectric particles] The dielectric particles may be oxide particles.
[0025] The oxide constituting the oxide particles is, for example, BaTi 1-x Zr x O3(0≦X≦0.5), SrBi2Ta2O9, (K 1-x Na x )NbO3(0≦X≦1), BiFeO 3、 CaCu3Ti4O 12 , Li 0.33 La 0.55 TiO3, Li 1.3 Al 0.3 Ti 1.7 P3O 12、 LiNbO3, etc.
[0026] The dielectric constant of the dielectric particles is preferably equal to or greater than 20, and more preferably equal to or greater than 30. When the dielectric constant of the dielectric particles is equal to or greater than 20, the cell resistance of the electricity storage device decreases and the durability improves.
[0027] The median diameter of the dielectric particles is preferably 0.3 μm or more and 1.0 μm or less, and more preferably 0.4 μm or more and 0.6 μm or less. When the median diameter of the dielectric particles is 0.3 μm or more and 1.0 μm or less, aggregation between the dielectric particles is unlikely to occur, and the contact area with the electrolyte is improved.
[0028] The content of the dielectric particles in the positive electrode mixture layer is preferably 0.1% by mass or more and 2% by mass or less, and more preferably 0.5% by mass or more and 1.0% by mass or less. When the content of the dielectric particles in the positive electrode mixture layer is 0.1% by mass or more, the cell resistance of the electricity storage device decreases and the durability improves, and when it is 2% by mass or less, the energy density of the electricity storage device improves.
[0029] [Positive electrode mixture layer] The positive electrode mixture layer contains a positive electrode active material and dielectric particles, and may further contain other components.
[0030] Examples of the other components include a solid electrolyte, a conductive assistant, and a binder.
[0031] The positive electrode active material is not particularly limited as long as it is capable of absorbing and releasing lithium ions. For example, LiCoO2, Li(Ni 5 / 10 Co 2 / 10 Mn 3 / 10 )O 2、 Li(Ni) 6 / 10 Co 2 / 10 Mn 2 / 10 )O 2、 Li(Ni) 8 / 10 Co 1 / 10 Mn 1 / 10 )O 2、 Li(Ni) 0.8 Co 0.15 Al 0.05 )O 2、 Li(Ni) 1 / 6 Co 4 / 6 Mn 1 / 6 )O 2、 Li(Ni) 1 / 3 Co 1 / 3 Mn 1 / 3 )O 2、 Examples include LiCoO4, LiMn2O4, LiNiO2, LiFePO4, lithium sulfide, and sulfur.
[0032] The positive electrode active material may have a bimodal particle size distribution, which improves the packing of the positive electrode active material and narrows the pore diameter distribution of the positive electrode of this embodiment.
[0033] A positive electrode active material having a bimodal particle size distribution can be obtained, for example, by mixing positive electrode active materials having different peaks in the particle size distribution.
[0034] [Positive electrode current collector] The positive electrode current collector is not particularly limited, but examples thereof include metal foil.
[0035] The metal that constitutes the metal foil may be, for example, aluminum.
[0036] <Manufacturing method of positive electrode> The method for producing the positive electrode of the present embodiment is not particularly limited, and a typical method in this technical field can be applied. For example, a method of applying a positive electrode mixture layer paste containing a positive electrode active material and dielectric particles onto a positive electrode current collector and then drying the applied paste can be mentioned.
[0037] After the positive electrode mixture layer is formed on the positive electrode current collector, a method generally used in the art can be applied. For example, the positive electrode current collector on which the positive electrode mixture layer is formed is pressed to obtain a positive electrode. At this time, the density of the positive electrode can be adjusted by pressing.
[0038] <Electricity storage device> The electricity storage device of this embodiment includes the positive electrode of this embodiment, a negative electrode, and an electrolyte solution.
[0039] Examples of the power storage device include secondary batteries such as lithium ion secondary batteries, and capacitors.
[0040] The negative electrode is not particularly limited, and any known negative electrode that can be applied to an electricity storage device can be used.
[0041] The electrolyte is not particularly limited, and any known electrolyte that can be applied to an electricity storage device can be used.
[0042] [Lithium-ion secondary battery] The lithium ion secondary battery of this embodiment includes the positive electrode of this embodiment, a negative electrode, an electrolyte, and a separator located between the positive electrode and the negative electrode.
[0043] In the lithium ion secondary battery of this embodiment, two types of materials are selected from materials capable of forming electrodes, and the charge / discharge potentials of the two types of materials are compared. The material exhibiting a more noble potential is applied to the positive electrode, and the material exhibiting a more base potential is applied to the negative electrode, thereby making it possible to form any battery.
[0044] The separator is not particularly limited, and any known separator that can be applied to lithium ion secondary batteries can be used. EXAMPLES
[0045] Examples of the present invention will be described below, but the present invention is not limited to these examples.
[0046] [Dielectric particles] After obtaining the dielectric particles from Toshima Manufacturing Co., Ltd., the dielectric particles that required adjustment of the median diameter were pulverized by a ball mill using IPA.
[0047] Table 1 shows the properties of the dielectric particles.
[0048] [Table 1]
[0049] [Method for measuring the dielectric constant of powder] The powder was introduced into a tablet press with a diameter (R) of 38 mm for measurement, and then compressed to a thickness (d) of 1 to 2 mm using a hydraulic press to form a green compact. powder The powder compact was molded so that the mass density of the powder compact / the true specific gravity of the powder x 100 was 40% or more. Next, the capacitance C of the powder compact at 25°C and 1 kHz was measured by the automatic balancing bridge method using an LCR meter. total The dielectric constant ε of the green compact was measured. total Next, the dielectric constant of vacuum, ε0, was calculated as 8.854×10 -12 , the relative dielectric constant of air ε air is set to 1, and the relative dielectric constant ε of the powder (actual volume portion) is calculated using the following equations (1) to (3). power was calculated. Contact area between powder compact and electrode A = (R / 2) 2 ×π (1) C total =ε total ×ε0×(A / d) (2) ε total =ε powder ×D powder +ε air ×(1-D powder) · · · (3)
[0050] [Median diameter (D 50 ) Measurement method The particle size distribution of the powder was measured using a particle size distribution measuring device MT3000II (manufactured by Microtrac). At this time, water was used as a solvent, the refractive index was set to 1.81, and the particle size value at a cumulative percentage of 50 was taken as the median diameter.
[0051] <Examples 1 to 5 and Comparative Examples 1 to 3> [Preparation of positive electrode] The dielectric particles, acetylene black (AB) as a conductive assistant, polyvinylidene fluoride (PVDF) as a binder, and polyvinylpyrrolidone (PVP) as a dispersant were premixed with N-methyl-2-pyrrolidone (NMP) as a dispersion medium, and then wet-mixed using a centrifugal mixer to obtain a premixed slurry. Next, LiNi 0.8 Co 0.1 Mn 0.1 After mixing O2 (NCM811) and the premixed slurry, a dispersion process was performed using a planetary mixer to obtain a positive electrode composite layer paste. The mass ratio of each component in the NCM811 positive electrode composite layer paste is shown in Table 2. Here, when NCM811 has a bimodal particle size distribution, it has peaks at 4 μm and 14 μm, and when it does not have a bimodal particle size distribution, it has a peak at 12 μm.
[0052] The positive electrode composite layer paste was applied to an aluminum foil as a positive electrode current collector, and then dried. Next, the dried positive electrode current collector was pressed by a roll press, and then dried in a vacuum at 120°C to form a positive electrode composite layer, thereby obtaining a positive electrode plate. The obtained positive electrode plate was punched out to a size of 30 mm x 40 mm to obtain a positive electrode.
[0053] [Preparation of negative electrode] An aqueous solution of carboxymethyl cellulose (CMC) as a binder and acetylene black (AB) as a conductive assistant were premixed using a planetary mixer. Next, natural graphite (NG) as a negative electrode active material was mixed, and then premixed using a planetary mixer. Next, water as a dispersion medium and styrene butadiene rubber (SBR) as a binder were added, and then a dispersion process was performed using a planetary mixer to obtain a negative electrode mixture layer paste. The mass ratio of each component in the negative electrode mixture layer paste was NG:AB:CMC:SBR=97.5:0.5:1.0:1.0. NG has a median diameter of 12 μm. Next, the negative electrode composite layer paste was applied to a copper foil as a negative electrode current collector, and then dried. Next, the dried negative electrode current collector was pressed by a roll press, and then dried in a vacuum at 130°C to form a negative electrode composite layer, thereby obtaining a negative electrode plate. The obtained negative electrode plate was punched out to a size of 32 mm x 42 mm to obtain a negative electrode.
[0054] [Preparation of lithium-ion secondary batteries] Aluminum laminate for secondary batteries (manufactured by Dai Nippon Printing) was heat-sealed and processed into a bag to obtain a container. Next, a laminate in which a separator was sandwiched between a positive electrode and a negative electrode was introduced into the inside of the container, and then an electrolyte was poured into the interface of each electrode. Next, the container was reduced in pressure to -95 kPa and sealed to produce a lithium-ion secondary battery. As the separator, a polyethylene microporous film coated on one side with alumina particles at a thickness of about 5 μm was used. As the electrolyte, a solution in which LiPF6 was dissolved as an electrolyte salt at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 30:30:40 was used.
[0055] <Positive electrode pore diameter distribution> The positive electrode was pretreated by vacuum drying at 120° C. for 12 hours, and then the pore diameter distribution of the positive electrode was measured by mercury intrusion porosimetry using an Autopore V9605 (manufactured by Micromeritics) in a pore diameter range of approximately 0.0036 to 200 μm. Here, the pore diameter of the positive electrode was calculated using the Washburn formula. Washburn formula: P×D=-4×σ×cosθ (P: pressure, σ: surface tension of mercury, D: pore diameter, θ: contact angle of the positive electrode with mercury) Here, the surface tension of mercury was 480 dynes / cm, and the contact angle of the positive electrode with mercury was 140°.
[0056] Fig. 1 shows the measurement results of the pore diameter distribution of the positive electrodes of Examples 1 to 5 and Comparative Examples 1 to 3. Here, the values shown in Fig. 1 are the peak pore diameters of each positive electrode.
[0057] <Cross-section observation of positive electrode> The cross sections of the positive electrodes of Example 1 and Comparative Example 1 were observed using an SEM.
[0058] Fig. 2 shows an SEM photograph of a cross section of the positive electrode of Example 1. Fig. 3 shows an SEM photograph of a cross section of the positive electrode of Comparative Example 1.
[0059] 2 and 3, it can be seen that the positive electrode of Example 1 has less space (area surrounded by dotted line) than the positive electrode of Comparative Example 1. Therefore, when the positive electrode of Example 1 is used, the proportion of the electrolyte in contact with the dielectric particles increases.
[0060] <Evaluation of initial performance of lithium-ion secondary batteries> The lithium ion secondary batteries of Examples 1 to 5 and Comparative Examples 1 to 3 were evaluated for initial performance as follows.
[0061] [Discharge capacity] The lithium-ion secondary battery thus fabricated was left at the measurement temperature (25°C) for 1 hour, and then constant current charging was performed at 12.4mA up to 4.2V, followed by constant voltage charging at a voltage of 4.2V for 1 hour. Next, the lithium-ion battery was left for 30 minutes, and then constant current discharging was performed at a current value of 12.4mA down to 2.5V. Next, the above operation was repeated 5 times, and the discharge capacity at the 5th discharge was taken as the discharge capacity (mAh). The current value at which the discharge could be completed in 1 hour for the obtained discharge capacity was taken as 1C.
[0062] [Cell resistance] The lithium ion secondary battery after measuring the discharge capacity was left at the measurement temperature (25°C) for 1 hour, and then constant current charging was performed at a charge rate of 0.2C, and the charge level (SOC (State of Charge)) was adjusted to 50% and left for 10 minutes. Next, pulse discharge was performed at a discharge rate of 0.5C for 10 seconds, and the voltage when discharged for 10 seconds was measured. Then, the horizontal axis was the current value and the vertical axis was the voltage, and the voltage when discharged for 10 seconds was plotted against the discharge rate of 0.5C. Next, the lithium ion secondary battery was left for 10 minutes, and then supplementary charging was performed to return the SOC to 50%, and the lithium ion secondary battery was left for 10 minutes. Next, the above operation was performed at each discharge rate of 1.0C, 1.5C, 2.0C, 2.5C, and 3.0C, and the voltage when discharged for 10 seconds was plotted against each discharge rate. Then, the slope of the approximation line obtained by the least squares method from each plot was taken as the cell resistance (mΩ).
[0063] <Evaluation of endurance performance of lithium-ion secondary batteries> The lithium ion secondary batteries of Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to the following evaluation of post-durability performance.
[0064] [Discharge capacity] In a thermostatic chamber at 45°C, the lithium-ion secondary battery was charged at a constant current of 1C to 4.2V, and then discharged at a constant current of 2C to 2.5V, with this operation being considered as one cycle. The above operation was repeated 500 cycles. Next, the temperature of the thermostatic chamber was changed to 25°C, and the lithium-ion secondary battery was left for 24 hours. Next, a constant current charge was performed at a charge rate of 0.2C to 4.2V, followed by a constant voltage charge at a voltage of 4.2V for 1 hour. Next, the lithium-ion secondary battery was left for 30 minutes, and then a constant current discharge was performed at a discharge rate of 0.2C to 2.5V, and the discharge capacity (mAh) was measured.
[0065] [Cell resistance] After measuring the discharge capacity, the lithium ion secondary battery was adjusted to a charge level (SOC (State of Charge)) of 50% in the same manner as in measuring the initial performance, and then the cell resistance (mΩ) was determined.
[0066] [Capacity maintenance rate] The ratio of the discharge capacity after endurance testing to the discharge capacity at the initial stage was calculated and defined as the capacity retention rate (%).
[0067] [Resistance change rate] The ratio of the cell resistance after endurance testing to the cell resistance at the initial stage was calculated and defined as the resistance change rate (%).
[0068] Table 2 shows the evaluation results of the initial performance and post-durability performance of lithium-ion secondary batteries.
[0069] [Table 2]
[0070] It can be seen from Table 2 that the lithium ion secondary batteries of Examples 1 to 5 have low cell resistance and high durability.
[0071] In contrast, the lithium ion secondary battery of Comparative Example 1 has a high cell resistance and low durability because the positive electrode mixture layer does not contain dielectric particles, and the lithium ion secondary batteries of Comparative Examples 2 and 3 have a high cell resistance and low durability because the peak pore diameter of the positive electrode is larger than the median diameter of the dielectric particles.
Claims
1. A positive electrode current collector and a positive electrode mixture layer, The positive electrode mixture layer includes a positive electrode active material and dielectric particles, The dielectric particles have a relative dielectric constant of 20 or more and a median diameter of 0.3 μm or more and 1.0 μm or less, a peak pore diameter less than or equal to the median diameter of said dielectric particles.
2. The positive electrode according to claim 1 , wherein the positive electrode mixture layer has a content of the dielectric particles of 0.1% by mass or more and 2% by mass or less.
3. 3. The positive electrode of claim 1 or 2, having a peak pore diameter of 0.1 μm or more and 0.6 μm or less.
4. 4. The positive electrode of claim 1, wherein the density is 3.4 g / cc or greater.
5. 5. The cathode of claim 1, wherein the cathode active material has a bimodal particle size distribution.
6. An electricity storage device comprising: the positive electrode according to claim 1 ; a negative electrode; and an electrolyte solution.
Citation Information
Patent Citations
Lithium secondary battery
JP2012209161A
A mixed oxide powder containing the elements lithium, manganese, nickel, and cobalt, and a method for producing the powder.
JP2013531602A
Non-aqueous lithium secondary battery
JP2016119180A
Lithium-ion secondary battery
JP2018029073A
Electrode, secondary battery, battery pack and vehicle
JP2019169252A